Application of Bradford's Law of Scattering to the Horticulture Literature: a Citation Study of Doctoral Dissertations 1991-2010 - Tunga, Santosh Kumar (Journal of Information and Knowledge, 2013)
Eighty doctoral dissertations submitted to the Bidhan Chandra Krishi Viswavidyalaya (BCKV) and Uttar Banga Krishi Viswavidyalaya (UBKV), West Bengal from 1991-2010 by the research scholars of horticulture are taken as the source materials. A total number of 10845 references were appended to the eighty dissertations, of which, 8437 were journal articles. A study on twenty-year data of journals cited by the horticulture scientists was carried out to examine the applicability of Bradford’s law of scattering. Applicability of Bradford’s law was tested. The journal distribution pattern of the horticulture doctoral dissertations does not fit the Bradford’s distribution pattern. The distribution of the journals in three zones was made and the number of references in each zone was then estimated.